The Art Declaration of Abstract-Figurative Metarealism - Dr. Gayané Manasyan (Research Retrieval and Academic Letters, 2025)
“ This is the art declaration written based on the exploration and the analysis of the paintings and art that I create formulated as Abstract-Figurative Metarealism. Abstract-Figurative Metarealism covers reality in the entire range of its actual and possible transformations freeing images through abstraction transgressing the borders of the figurative art. Abstract-Figurative Metarealist creates compositions as a result of explorations of superconscious imagery.” (Gayané Manasyan, 2024, pg. 16)